A middleware for workload-aware manipulation of RDF data stored into NoSQL databases - Santana, Luiz Henrique Zambom (2019)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Ciência da Computação, Florianópolis, 2019.